EFL students’ voices on digital peer feedback - Dyah Ayu Aprilianti, Berliana; Hidayatulloh, Sibakhul Milad Malik (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
Education and technology have been tailed by some conditions. Some parts in education are technologized including peer feedback activity, but the use of peer feedback combined with e-learning needs to be reviewed in terms of its practical use. The affordance of technology has enabled peer feedback to take place online. Despite the potential benefits that online peer feedback may offer, there is a lack of studies on the topic. Therefore, this paper aims to explore students’ perspectives on the benefits of online peer feedback. This research was done qualitatively. Interview to six students of English Language Education Department was conducted to gain the data. The academic year 2018/2019. In selecting the participants, purposive sampling was applied. The finding of this study revealed that the use of technology particularly in giving peer feedback brought some benefits e.g., increasing students’ autonomy and reviving student’s critical thinking. Besides, the cons of this phenomenon were that students felt the activity ruined their energy to stay focused in front of the screen to give others a review. Some suggestions in the last part of this paper also appeared as the researchers respond to this phenomenon.